« first day (3952 days earlier)      last day (1289 days later) » 

14:16
@user21820 I see now why you say it is an equivalence, instead of an implication:
If x^2 = 4:
  (x+2)·(x−2) = 0
  If ¬(x = 2 ∨ x = 6000):
    If x ≠ 2:
      (1/(x−2))·(x+2)·(x−2) = (1/(x−2))·0
      x+2 = 0
      x = –2
      x = 2 ∨ x = –2
      ⊥
    x = 2
    x = 2 ∨ x = 6000
  x = 2 ∨ x = 6000
I can't complete the other direction :-)
14:29
Given x ∈ ℝ:
  If x^2 = 4:
    (x+2)·(x−2) = 0
    If ¬(x = 2 ∨ x = 6000):
      If x ≠ 2:
      x = 2
      x = 2 ∨ x = 6000
      ⊥
    x = 2 ∨ x = 6000
    ...
@user21820 Thank you. Now, this wrong proof should be correct :-)
@user21820 I am trying to see why your system is preventing me from proving false statements.
That's an issue I had with disjunctions. Your comments clarifies it.
@F.Zer It's still wrong. Do you want me to delete all of them since you know?
@user21820 Of course. Delete all of them. Could you show me how to prove "∀ x ∈ ℝ ( x^2 = 4 ⇒ x = 2 ∨ x = 6000 )" ? Using an implication, of course.
If that is not provable, then I am missing something.
@F.Zer It's not provable!!! Why are you trying to prove it?
I mean, I do know that I can't prove "∀ x ∈ ℝ ( x^2 = 4 ⇔ x = 2 ∨ x = 6000 )"
8 messages moved from Basic Mathematics
14:38
@user21820 Could you please point out where my proof when wrong ? There must be some incorrect inference step.
@F.Zer It's so short you should find it yourself.
@user21820 I will do it, now.
@user21820 I derived this incorrect statement "x = 2 ∨ x = 6000". I see it, now. I can't prove it. This was very educational.
The previous step was "x = –2".
I need to (at least) include the original two solutions, as you say. Otherwise, I can't prove it.
So do you want to keep the above comments?
@user21820 Delete everything :-)
13 messages moved from Basic Mathematics
 
8 hours later…
22:30
Prove there exists a surjective function from N to Z.

1 p ∈ F <-> ∃n ∈ N ∃z ∈ Z ^ p = ⟨n,z⟩ ^ φ(n,z)
2 F := {⟨x,y⟩:x∈N ^ y ∈ Z ^ φ(x,y)} \\shorthand for 1
3 φ(x,y) := ∃z∈N [(x=2z ^ y=z) v (x=2z+1 ^ y=-z)]

\\Prove F is a function:
4 N x Z = {x: n ∈ N ^ z ∈ Z ^ x = ⟨n, z⟩}
5 ∴F ⊆ N x Z \\from 2, since φ(n,z) is just a restriction on which n,z satisfy ⟨n,z⟩
6 ∴F ∈ P(N x Z)

7 If ⟨x',y_1⟩, ⟨x', y_2⟩ ∈ F:
8	φ(x, y_1) ^ φ(x, y_2)
9	z_1 := z_1 ∈ N ^ (x'=2z_1 ^ y_1=z_1) v (x'=2z_1 +1 ^ y_1=-z_1)	\\from φ's definition

« first day (3952 days earlier)      last day (1289 days later) »